2009
DOI: 10.1137/080725726
|View full text |Cite
|
Sign up to set email alerts
|

On Computing the Critical Coupling Coefficient for the Kuramoto Model on a Complete Bipartite Graph

Abstract: We extend recent results [50] on the existence of global phase-locked states (GPLS) in the Kuramoto model on a complete graph to the case of a complete bipartite graph. In particular, we prove that, for the Kuramoto model on a complete bipartite graph, the value of the critical coupling coefficient can be determined by solving a system of two nonlinear equations that do not depend on the coupling coefficient. We show that the said system of equations can be solved using an efficient algorithm described in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 50 publications
1
62
0
Order By: Relevance
“…We remark that Verwoerd and Mason also extended the implicit formulae (44)- (45) to complete bipartite graphs (Verwoerd and Mason, 2009, Theorem 3) and infinite-dimensional networks (Verwoerd and Mason, 2011, Theorem 4). Moreover, they provided bisection algorithms to compute K critical with predefined precision in a finite number of iterations.…”
Section: Exact and Implicit Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We remark that Verwoerd and Mason also extended the implicit formulae (44)- (45) to complete bipartite graphs (Verwoerd and Mason, 2009, Theorem 3) and infinite-dimensional networks (Verwoerd and Mason, 2011, Theorem 4). Moreover, they provided bisection algorithms to compute K critical with predefined precision in a finite number of iterations.…”
Section: Exact and Implicit Conditionsmentioning
confidence: 99%
“…In general, concise and accurate results are known only for specific topologies such as complete graphs (as discussed in the previous section), linear chains (Strogatz and Mirollo, 1988), highly symmetric ring graphs (Buzna et al, 2009), acyclic graphs (Dekker and Taylor, 2013), and complete bipartite graphs (Verwoerd and Mason, 2009) with uniform weights. For arbitrary coupling topologies, the literature contains only sufficient conditions Kumagai, 1980, 1982;Jadbabaie et al, 2004;Dörfler and Bullo, 2012b) as well as numerical and statistical investigations for large random net-11 More precisely, the incremental norms B T ω p are seminorms in R n and proper norms in the quotient space 1 ⊥ n .…”
Section: Survey Of Synchronization Metrics and Conditionsmentioning
confidence: 99%
“…[18][19][20], necessary and sufficient conditions are given for fixed points to exist for the finite size Kuramoto model for complete and bipartite graphs, and explicit upper and lower bounds of K c (N ) for these systems were also computed, followed by providing an algorithm to compute K c (N ). For the complete graph, similar results were presented in [21,22], where it was additionally shown that there is exactly one single stable equilibrium for K > K c (N ).…”
mentioning
confidence: 99%
“…Verwoerd and Mason also extended their results to bipartite graphs [24] but did not carry out a stability analysis. The formulas (8)- (9) can be reduced exactly to the implicit selfconsistency equation derived by Mirollo and Strogatz in [20] and by Aeyels and Rogge in [21], where additionally a local stability analysis is carried out.…”
Section: Implicit and Exact Bounds For The Finite Dimensional Kuramentioning
confidence: 99%
“…. , n} and for all t ≥ 0 [9], [19], [21], [23], [24]. Other commonly used terms in the vast synchronization literature include full, exact, or perfect synchronization (or even phase locking [3]) for phase synchronization and frequency locking, frequency entrainment, or partial synchronization for frequency synchronization.…”
Section: The Kuramoto Model Of Coupled Oscillatorsmentioning
confidence: 99%